Design and synthesis of tubulin-binding agents, and their incorporation into novel dual-acting hybrid molecules targeting the tumour vasculature - Coogan, Adrian (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
This thesis involves the design and synthesis of tubulin binding agents, which aside from their anti-proliferative impact, seek to induce anti-vascular and anti-angiogenic responses on the unique vasculature derived by a growing tumour mass. Once synthesised, studies were conducted on the incorporation of the most active tubulin binding agents into a novel series of hybrid drugs or designed multiple ligands, which serve to complement their therapeutic effect. The thesis is introduced by a comprehensive overview of the process of angiogenesis, the tumour vasculature network, and the myriad of differences between tumour blood vessels and those of normal vascular systems. Also discussed are the two main interrelated strategies for disrupting the microvasculature of tumours; the anti-angiogenic and anti-vascular approaches, with examples provided for each. The benefit of combination and hybrid therapies is outlined, with particular regard to each side of the concepts we intended to implement; dual targeting of both the tubulin subunits which can eventually cause occlusion of a tumour blood vessel, and the multifunctional enzymatic receptor Aminopeptidase N (APN), expressed solely on tumour vasculature undergoing angiogenesis but not on normal, quiescent vasculature. The introductory chapter ends by outlining the aims of the thesis.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin